"Itô's lemma" and the Bellman equation for Poisson processes an applied view - Sennewald, Ken; Wälde, Klaus 1966- (CESifo working paper, 2006)
Using the Hamilton-Jacobi-Bellman equation, we derive both a Keynes-Ramsey rule and a closed form solution for an optimal consumption-investment problem with labor income. The utility function is unbounded and uncertainty stems from a Poisson process. Our results can be derived because of the proofs presented in the accompanying paper by Sennewald (2006). Additional examples are given which highlight the correct use of the Hamilton-Jacobi-Bellman equation and the change-of-variables formula (sometimes referred to as Ito's-Lemmaʺ) under Poisson uncertainty.